Achievement-Based School Principal Leadership in Improving the Quality of Education at the Buffer Schools of the Nusantara Capital City (IKN): Achievement-Based School Principal Leadership in Improving the Quality of Education at the Buffer Schools of the Nusantara Capital City (IKN) - Budiman Budiman; Azainil Azainil; Haeruddin Haeruddin; Laili Komariyah; Amir Masruhim; Usfandi Haryaka (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
This study aims to describe and analyze the planning, organizing, strategies, impacts, and challenges of performance-based school principal leadership at SMP Negeri 27 Penajam Paser Utara in efforts to improve the quality of education. The research employs a qualitative approach using a case study method. Data collection techniques include observation, interviews, and documentation. The findings are as follows: (1) Performance-based leadership at SMP the Buffer Nusantara Capital City (Ibu Kota Nusantara) emphasizes continuous teacher competency development through routine training and systematic evaluation using a participatory transformational approach; (2) Leadership organization involves structured and synergistic resource management, supported by ongoing monitoring and program evaluation to maintain the quality of education; (3) Leadership strategies focus on strengthening teachers’ professional capacity, developing a culture of innovative quality, implementing school-based management (SBM), engaging the community, and managing facilities that support optimal learning; (4) The impact of performance-based school principal leadership is evident in improved learning quality, school community motivation, discipline, academic achievement, and innovation; (5) Challenges in performance-based leadership include limited resources, diverse teacher motivation, resistance to innovation, and heavy workloads, which are addressed through routine evaluations, effective communication, and conflict and time management strategies